2005
DOI: 10.1152/ajpheart.01091.2004
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity produces attenuated baroreflex-mediated pressor, chronotropic, and inotropic responses in mice

Abstract: Whether myocardial contractile impairment contributes to orthostatic intolerance (OI) is controversial. Accordingly, we used transient bilateral carotid occlusion (TBCO) to compare the in vivo pressor, chronotropic, and inotropic responses (parts 1 and 2) to open-loop selective carotid baroreceptor unloading in anesthetized mice. In part 3, in vitro myocyte responses to isoproterenol in mice exposed to hindlimb unweighting (HLU) for approximately 2 wk were determined. Heart rate (HR) and mean arterial pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…One group of the rats (n ϭ 40) was subjected to tail suspension to simulate microgravity, while the control (n ϭ 40) was maintained in room air. The technique of tail suspension (22) with modification from our collaborative laboratory has been described in detail previously (13,20). The animals were maintained at about Ϫ30°head-down tilt with their hindlimbs unloaded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One group of the rats (n ϭ 40) was subjected to tail suspension to simulate microgravity, while the control (n ϭ 40) was maintained in room air. The technique of tail suspension (22) with modification from our collaborative laboratory has been described in detail previously (13,20). The animals were maintained at about Ϫ30°head-down tilt with their hindlimbs unloaded.…”
Section: Methodsmentioning
confidence: 99%
“…The depressed contractility may be due to the changes of cardiac tissue, the low cardiovascular response to low circulating blood volume, and the impaired regulation of cardiac function. It is well known that ␤-adrenoceptor is a predominant receptor in regulation of cardiac function, and recent studies have suggested that the responsiveness of cardiac contractility to ␤-adrenoceptor stimulation is reduced after weightlessness (13,26).…”
mentioning
confidence: 99%
“…Previous studies have suggested that arterial baroreflex control of HR is diminished in heart failure, 11,21) and that the contribution of baroreflex control in myocardial contractility is markedly impaired in animals with a lower baseline inotropic state. 22) Furthermore, in heart failure, baroreflex changes in cardiac output are less related to changes in HR and more related to changes in stroke volume. 23) Milrinone is considered to exert a positive inotropic action and to decrease left ventricular endsystolic pressure reflecting the decrease in left ventricular afterload.…”
Section: Discussionmentioning
confidence: 99%
“…One group of rats (n ϭ 44) was subjected to tail suspension to simulate microgravity, whereas the control (normal group, n ϭ 44) was maintained at ambient air. The technique of tail suspension (3) with modifications from our collaborative laboratory has been previously described in detail (10,13). Animals were maintained at about Ϫ30°C head-down tilt, with their hindlimbs unloaded.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that the ␤-adrenoceptor is a predominant receptor in regulation of cardiac function. Recent studies suggested that the responsiveness of cardiac contractility to ␤-adrenoceptor stimulation is reduced after weightlessness (10,11). Depressed ␤-adrenoceptor responsiveness may be due to downregulation of the ␤-adrenoceptor itself or to the impaired postreceptor events.…”
mentioning
confidence: 99%